IMPROVING THE QUALITY OF GLUTEN-FREE BREAD MANUFACTURED FROM PROSO MILLET USING HYDROCOLLOIDS - E. K. Hammood; J. M. Nasser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of this study was to investigate the role of some hydrocolloids in improving the physical and sensory properties of gluten-free bread manufactured from millet flour. Whole grain millet flour (T2), whole grain millet flour with xanthan gum (T3), whole grain millet flour with guar gum (T4), unprocessed millet flour with extraction rate of (71%) with xanthan gum (T5), unprocessed millet flour with extraction rate of (71%) with guar gum (T6) ,were used  to prepare gluten free bread beside another treatment manufactured by the same ingredients with replacing the sugar by glycerol (T7).The wheat flour was used as standard (T1).  The results of the chemical composition showed that whole-grain Proso millet flour had higher percentages of fat, protein, ash and fiber, and  lower moisture and carbohydrates content, in comparison to wheat flour. The amylose content were (38.46 - 26.25%) for wheat flour and whole grain millet flour respectively, which indicates that Proso millet is a non-waxy cultivar. The results of the physical properties of the baking product, represented by volume and specific volume, showed that T1 and T3 outperformed over the rest  treatments. A sensory evaluation indicated that gluten-containing bread was more acceptable to consumers. Followed by gluten-free bread with xanthan gum, as the total scores for  these two treatment were (94.73 , 85.92 ). While for T2, T3, T4, T6, T7 treatments were (44.44, 77.62, 54.72, 62.39,  82.45).